(3GdJbQjQGJs - (3GdcdHGSj GdfLaj, eMeO EHQGgje Hf MSjf GdcdHGSj GdfLaj, hdO SfI (B1322(3g`s ((3HNW GdeDdas)
(3ChdgG (B:s
(3ChdgG(B: (3GYde Cfg bO LQJ YGOI Cgd Gdafhf Cfge jbOehf bHd GdTQhY aj Gdaf HjGf ehVhYg hZGjJg hPcQ JYQjag hRGO GdeJCNQhf efge ebOeI QGHYI gj HjGf eQJHI Gdafs
(3BNQgG (B:s
(3BNQgG(B: (3hbO JdNU Cf GdJQJjH dOjfG (B.. (3aj eSFdJjf ef eSGFd GdJRGMe hgeG eSFdI GdVOjf heSFdI GdebOeI (B.. (3Ohf HbjI GdeSGFd hHPdc NJGe GdeHMK GdChd ef eHGMK GdCdaGXs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdPQjYI, L (B4: 268s
(3GdPQjYI, L (B4: 268s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3CUhd Gdabgs